(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
The African Court on Human and Peoples’ Rights is a distinct body that protects human rights and develops jurisprudence in international and regional law. It is on this basis that it often awards compensation for human rights violations. However, while the Court gives reasons for compensation for pecuniary loss, it does not do so for nonpecuniary loss. With the aid of a conceptual approach, the contribution evaluates the argument that the Court’s failure to give reasons for compensation for nonpecuniary loss indicates a lack of clarity. With the aid of Lucien Ikili Rashidi v Tanzania (2015), Mtikila v Tanzania (2011), Norbert Zongo v Burkina Faso (2015), Lohe Issa Konate v Burkina Faso (2016) and Armand Guehi v Tanzania (2015) this contribution evaluates the Court’s approach to the grant of compensation for nonpecuniary loss. The Court’s failure to give reasons in instances of nonpecuniary loss affects the application of the rule of law in the adjudication of cases. This contribution argues that the Court’s jurisprudence presents an inconsistent approach to this problem. To substantiate this argument, this case discussion gives the facts and holding in Lucien Ikili Rashidi and identifies the lack of clarity by the African Court in dealing with non-pecuniary loss. This is followed with a close evaluation of the four earlier cases of Mtikila, Zongo, Konate and Guehi. A two-stage approach in dealing with compensation for the non-monetary loss is proposed. First, a finding of the existence of a human rights violation should be presumed sufficient to warrant the award of compensation for nonpecuniary loss. Second, the Court should then evaluate the amounts claimed against the principles of equity and the circumstances of the case.